Ras-Related C3 Botulinum Toxin Substrate 1 Combining With the Mixed Lineage Kinase 3- Mitogen-Activated Protein Kinase 7- c-Jun N-Terminal Kinase Signaling Module Accelerates Diabetic Nephropathy - Ying, Changjiang; Dai, Jiao; Fan, Gaoxia; Zhou, Zhongyuan; Gan, Tian; Zhang, Yusheng; Song, Yuanjian; Zhou, Xiaoyan (Frontiers in Physiology, 2021)
Abstract Ras-related C3 botulinum toxin substrate 1 (RAC1) activation plays a vital role in diabetic nephropathy (DN), but the exact mechanism remains unclear. In the present study, we attempted to elucidate the precise mechanism of RAC1 aggravating DN through cellular and animal experiments. In this study, DN was induced in mice by streptozocin (STZ, 150 mg/kg) intraperitoneal injection, and special RAC1 inhibitor NSC23766 was given by tail vein. Biochemical indicators, cell activity and apoptosis and the morphology change of kidney were detected. The expression of p-JNK, NF-κB and Cleaved caspase-3 were tested, as well as the interaction of RAC1 and MLK3-MKK7-JNK signal module were determined. Furthermore, the co-localization and direct co-interaction of RAC1 and MLK3 were also confirmed. Results showed RAC1 accelerates renal damage and increases the expression of p-JNK, NF-κB and Cleaved caspase-3. However, inhibition of RAC1 ameliorated DN by down-regulating p-JNK, NF-κB and Cleaved caspase-3. Besides that, RAC1 promoted the assembly of MLK3-MKK7-JNK, and NSC23766 blocked the interaction of RAC1 and MLK3-MKK7-JNK, and inhibit the assembly of MLK3-MKK7-JNK signal module. Furthermore, RAC1 combined with MLK3 directly, but mutant (Y40C) could inhibit RAC1 interact with MLK3. Our study demonstrated that RAC1 combining with MLK3 activates MLK3-MKK7-JNK signal module and accelerates DN occurrence and development, and serine Y40 is an important site for RAC1 binding to MLK3. This study illustrates the cellular and molecular mechanisms of RAC1 accelerating DN and provides evidence of targeted therapy of DN.